Brand managers' relations with industrial service providers in pharmaceutical and other companies - Panigyrakis, George G.; Veloutsou, Cleopatra A. (My University, 1999)
Focuses on the relations that product managers, as industrial buyers, develop with industrial service providers (advertising, promotional and marketing research agencies, lawyers, other consultants and distribution channels) in different business sectors in Greece. Investigates how brand managers in the pharmaceutical and other fast-moving consumer goods industries view their relationships with their various interfaces, by analysing the allocation of their working time, the level of contact, and the perceived significance and quality of relationships with their interfaces. The results indicate that there are differences in the development of relationships amongst the sectors analysed.
Keywords: Brands; Business-to-business marketing; Greece; Pharmaceuticals; Product management; Professional services